The PENDAMPINGAN KUASA HUKUM BAGI TERDAKWA YANG DIJATUHI HUKUMAN 7 TAHUN PERJARA DALAM SUATU TINJAUAN PUTUSAN NOMOR 28/PID.SUS/2020/PN.MLG - Manulung Bansage Immanuel Papara, Satrya; Ratnawati Gultom, Elfrida (Universitas Ekasakti, 2023)
Defendants who are sentenced to more than 5 years in prison must get legal assistance. the formulation of the problem is What is the Consideration of the Panel of Judges on Case Number 28/Pid.Sus/2020/PN.Mlg) Concerning the Accompaniment of Defendant Rahman Suedi in the case of drug abuse according to Article 127 of Law Number 35 of 2009? and How to deal with abuse addicts and victims of narcotics abuse. In writing this paper, the research method used is normative and analyzed descriptively using secondary data. Inductive conclusions are drawn. The results of the research into the considerations of the Panel of Judges on the Case.